PENDIDIKAN METODE PEMBELAJARAN PRESFEKTIF IBNU KHALDUN - mahmudi, Nurmahmudi Nur (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2023)
In thinking about the learning of a great figure, Ibnu Khaldun, the author will describe what is meant by learning or education for Ibn Khaldun, what are the methods of learning or education for Ibn Khaldun, and how is the application of learning from Ibn Khaldun? the learning method used by Ibnu Khaldun, how is the relevance of learning methods at the present time. In this study using study library, the benefits of this discussion can provide knowledge as well as understanding to readers and as a scientific contribution for educators and students regarding learning education methods according to Ibnu Khaldun as inspiration in upholding quality education in Indonesia.